Nanotechnology Future and Present in Construction Industry: Applications in Geotechnical Engineering - Hasan, Umair; Chegenizadeh, Amin; Nikraz, Hamid (IGI Global, 2016)
After the introduction of nanotechnology, it has been widely researched in geotechnical engineering field. This chapter aims to study these advancements with specific focus on geotechnical applications. In-situ probing of soil and rock masses through nanomaterials may help in providing better safeguards against natural hazards. The molecular dynamics and finite element methods may also be used for the modelling of the nanostructures to better understand the material behavior, causing a bottom-up approach from nano to macroscopic simulations. Nanoclays, nano-metallic oxides and fibers (carbon nanotubes) can enhance the mechanical characteristics of weak, reactive and soft soils. Nanomaterials may also be used for improving the performance of reinforced concrete pavements by enhancing the thermal, mechanical and electrical characteristics of the concrete mixes. The chapter presents a review of the current researches and practices in the nano-probing, nanoscale modelling and application of nanomaterials for soil, pavement concrete mortar and subgrade stabilization.